Recent Advances in Agronomic and Physio-Molecular Approaches for Improving Nitrogen Use Efficiency in Crop Plants - Javed, Talha; I, Indu; Singhal, Rajesh Kumar; Shabbir, Rubab; Shah, Adnan Noor; Kumar, Pawan; Jinger, Dinesh; Dharmappa, Prathibha M.; Shad, Munsif Ali; Saha, Debanjana; Anuragi, Hirdayesh; Adamski, Robert; et al. (Frontiers in Plant Science, 2022)
The efficiency with which plants use nutrients to create biomass and/or grain is determined by the interaction of environmental and plant intrinsic factors. The major macronutrients especially nitrogen (N) limiting plant growth and development (1.5-2% of dry biomass) and have a direct impact on global food supply, fertilizer demand and concern with environment health. In the present time the global consumption of N fertilizer is nearly 120 MT (million tons) and the N efficiency ranging from 25 to 50% of applied N. The dynamic range of ideal internal N concentrations is extremely large, necessitating stringent management to ensure that its requirements to meet across various categories of developmental and environmental situations. Furthermore, approximately 60 per cent of arable land is mineral deficient and/or mineral toxicity around the world. The use of chemical fertilizers adds the cost of production for the farmers and also increases the environment pollution. Therefore, present study focused on the advancement in fertilizers approaches, comprises the use of biochar, zeolite, customized nano and bio-fertilizers which had shown effective in improving nitrogen use efficiency (NUE) with lower soil degradation. Consequently, adopting precision farming, crop modelling and use of remote sensing technologies such as chlorophyll meter, leaf color chart etc. assist in reducing the application of N fertilizer. This study also discussed the role of crucial plant attributes such as root structure architecture in improving the uptake and transport of N efficiency. The crosstalk of N with other soil nutrient play crucial role in nutrient homeostasis, which is also discussed thoroughly in this analysis. At the end, this review highlights the more efficient and accurate molecular strategies and techniques such as N transporters, transgenes, and omics, which are opening up intriguing possibilities for the detailed investigation of the molecular components that contribute to nitrogen utilization efficiency, thus expanding our knowledge of plant nutrition for future global food security.